BOYONG DEWI SRI TRADITION In KUMENDUNG VILLAGE, MUNCAR, BANYUWANGI, EAST JAVA - D.E, Relin (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Boyong Dewi Sri is one of the traditionsof the Javanese community whichis specifically done to welcome the rice harvest. During the rice harvest, the Java community in welcoming the blessings bestowed by Hyang Murbeng Dumadi always manifested in the form of salvation. The hope expressed by the Javanese community through their salvation is the harvest is abundant. Boyong Dewi Sri Tradition is usually implemented by farmers when the rice plants are yellowed or aged six months after planting. Boyong Dewi Sri Tradition still survive because it implies theological sense, as well as an ancestral cultural heritage that is believed to be relevant throughout ages. Boyong Dewi Sri Tradition own uniqueness and superiority. Its uniqueness is apparent on its implementation, which is carried out by the whole community and all religions, whether Muslim, Hindu, Buddhist and Christian. While his lead is that, despite all religions participate in the tradition of Boyong Dewi Sri, but there is no significant conflict occured.